Вплив типу полиці на агротехнічні показники роботи двох’ярусного плуга - Тищенко, Сергій Сергійович; Tyshchenko, Serhiy; Сова, Наталія Анатоліївна; Sova, Nataliya (Дніпровський державний аграрно-економічний університет, 2016)
Розглянуто геометричну модель лінійчастої поверхні полиці плуга, яка утворюється рухом прямолінійної твірної та має спільну точку з напрямною кривою. Геометрична модель поверхні базується на умові торсовості, до якої входить коефіцієнт кривини. На основі моделі виготовлено напівгвинтовий корпус нижнього ярусу двох’ярусного плуга, який на випробуваннях показав перевагу над культурним корпусом щодо загортання рослинних решток. The use of double-deck plow is plant residues plowing to a depth from which they are not drawn on field surface at further processing, providing increased nutrients in the soil and water reserves. The quality of treatment depends on the type of surface setter bulks that are set on the top and bottom of plow tiers. Double-deck plows that are in production, have arable frame upper and lower tiers after classical method of cylindroid surface. Instead of the existing cylindroid surface it is proposed ruled surface that is formed by movement in the space of straight lines having a common point of the guide curve. Generating is set on planes by its projections. Geometric pattern of surface connects the position settings of projection generators with coordinates of guide curve common point. Based on the conditions of develop surface, which includes the curvature coefficient, derived differential equation provisions projections generators. Integrating of this equation allows with known projection angle and coordinates of joint generatrix points on the same plane to determine the angle of projection generatrix on another plane and build surface. Curvature factor allows to design surface curvature which varies significantly, particularly when the coefficients curvature is zero the surface will be develop. With the developed model it is designed and manufactured half screw setter of lower housing component. Comparative studies of tiered plows agrotechnical data with arable frames and arable frames with a half screw combination found advantage of a plow with a half screw setter.At the working speed of 2,8 m / s and at a depth of 22 cm the depth of plant residues plowing with half screw setters was 15,9 cm, and with arable was 14,6, which is 6,41 % more. Percentage of plant residues plowing with half screw setters was 98,9 %, and with arable was 96,1 %, which is 4,3 % higher. Increased data are explained due to the fact that on the half screw setter surface the soil moves in a larger order. Thus, the proposed model surface allows to design plowing setter frames with improved agrotechnical data.
The influence of setter type on agrotechnical data of double-decker plow work
Keywords: двох’ярусні плуги; double-deck plow; геометрична модель поверхні; geometric pattern of surface; полиці; setter; агротехнічні прийоми; agrotechnical practices; загортання решток; residues plowing